Addressing conservation practice limitations and trade‐offs for reducing phosphorus loss from agricultural fields. Issue 2 (30th July 2022) - Kleinman, Peter J. A.; Osmond, Deanna L.; Christianson, Laura E.; Flaten, Don N.; Ippolito, James A.; Jarvie, Helen P.; Kaye, Jason P.; King, Kevin W.; Leytem, April B.; McGrath, Joshua M.; Nelson, Nathan O.; Shober, Amy L.; et al.
Abstract: Conservation practices that reduce nutrient and soil loss from agricultural lands to water are fundamental to watershed management programs. Avoiding trade‐offs of conservation practices is essential to the successful mitigation of watershed phosphorus (P) losses. We review documented trade‐offs associated with conservation practices, particularly those practices that are intended to control and trap P from agricultural sources. A regular theme is the trade‐off between controlling P loss linked to sediment while increasing dissolved P losses (no‐till, cover crops, vegetated buffers, constructed wetlands, sediment control basins). A variety of factors influence the degree to which these trade‐offs occur, complicated by their interaction and uncertainties associated with climate change. However, acknowledging these trade‐offs and anticipating their contribution to watershed outcomes are essential to the sustainability of conservation systems. Core Ideas: Avoiding the trade‐offs of conservation practices is essential to successful watershed outcomes. We review trade‐offs associated with conservation practices intended to trap P. A regular theme is the trade‐off between controlling P loss linked to sediment while increasing dissolved P losses.